MEDIUM TERM SOFT WHEAT MARKET OUTLOOK IN THE REPUBLIC OF CROATIA - Sudarić, Tihana; Kranjac, David; Zmaić, Krunoslav (Journal of Agricultural Sciences (Belgrade), 2021)
With Croatia's accession to the European Union (EU), numerous changes have taken place within the key agricultural markets. This primarily relates opening of the domestic market and adjustment of production and business within the EU single market, introduction of Common Agricultural Policy measures and instruments and convergence of domestic agri-food product prices. Sophisticated tools such as partial equilibrium (PE) econometric models are commonly used in the impact assessments of the integration processes, and for development of medium-term market outlook simulations. The AGMEMOD (PE) model is used to develop a simulation of the soft wheat market outlook in the Republic of Croatia until 2030. The model results simulate future trends of main agrarian policy indicators (sown area, production, yield, import, export and average producer price) on the soft wheat market. Croatian soft wheat market outlook assumes ceteris paribus market conditions with the existing structure of agricultural policy until the end of simulated period.Main findings of the simulated outlook indicate a slight growth trend of sown areas, continued growth of yield and production along with soft wheat exports increase in Croatia by 2030 compared to 2018. Also, Croatian of soft wheat self-sufficiency degree is expected to be 114% by the end of the simulated period.
Keywords: Tržište meke pšenice, pregled tržišta, parcijalna ravnoteža, simulacija, AGMEMOD